2021
DOI: 10.3390/app11073256
|View full text |Cite
|
Sign up to set email alerts
|

Sialic Acid as a Biomarker Studied in Breast Cancer Cell Lines In Vitro Using Fluorescent Molecularly Imprinted Polymers

Abstract: Sialylations are post-translational modifications of proteins and lipids that play important roles in many cellular events, including cell-cell interactions, proliferation, and migration. Tumor cells express high levels of sialic acid (SA), which are often associated with the increased invasive potential in clinical tumors, correlating with poor prognosis. To overcome the lack of natural SA-receptors, such as antibodies and lectins with high enough specificity and sensitivity, we have used molecularly imprinte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Our binding results show that SA-MIPs with a silica-coated PS core have a more pronounced tendency to conjugate with cancer cells, presumably due to their smaller size and better suspensibility. Previous work in our group using other SA-MIP batches with a larger size did not show the same binding efficiency [103,[119][120][121]. Optimization of the SA-MIPs synthesis protocol improved the binding features and specificity as shown by our results, and in a related paper by Kimani et al [81].…”
Section: Binding Of Lectins and Sa-mips To Cancer Cell Linessupporting
confidence: 75%
“…Our binding results show that SA-MIPs with a silica-coated PS core have a more pronounced tendency to conjugate with cancer cells, presumably due to their smaller size and better suspensibility. Previous work in our group using other SA-MIP batches with a larger size did not show the same binding efficiency [103,[119][120][121]. Optimization of the SA-MIPs synthesis protocol improved the binding features and specificity as shown by our results, and in a related paper by Kimani et al [81].…”
Section: Binding Of Lectins and Sa-mips To Cancer Cell Linessupporting
confidence: 75%
“…This was unexpected as B3GNT2 is reported to act on LacNAc acceptors on Nglycans, O-glycans, and glycolipids. 29 Since many cancer cell lines have truncated O-glycan structures, 55,56 we hypothesized that the apparent N-glycan specificity was attributed to the HS-578-T breast cancer cell line not displaying extended O-glycan structures that could serve as suitable acceptor sites for B3GNT2. Thus, GlcNAz-engineered HEK293T cells were also analyzed by streptavidin immunoblotting (Figure 4D).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This finding confirms the selectivity of the MIP particles for binding SA. We recently demonstrated the novel use of SA conjugates ME1057 and ME0970 by pre-treating the SA-MIPs (200 nm) with these SA conjugates as inhibitors [30]. It has also been shown that the titration of SA-MIPs with possible competitors GalNAc and glucose did not induce a fluorescence increase [22].…”
Section: Discussionmentioning
confidence: 99%